(untitled) (ENVIRONMENT. TECHNOLOGY. RESOURCES. Proceedings of the International Scientific and Practical Conference, 2024)
The present article is part of an in-depth scientific study focused on the evolution of officer training in the Bulgarian military school from 1878 to the present day. The subject of this report is the role of the military school in the developing system of national security in the period 1878-1885. The purpose of the report is to determine the contribution of the military school to national security based on the analysis of quantitative and qualitative indicators. To achieve the goal, the following research tasks have been formulated: 1. To carry out a study of the available military-historical archival funds and units to establish the parameters of the quantitative and qualitative indicators of the study. 2. Based on the analysis of the career development of officers who successfully graduated from the military school, to determine their contribution to national security for the period of study. The research methodology covers the use alone or in combination of the generally accepted scientific methods of analysis and synthesis, comparison, induction and deduction, historical references, studies of specialized publications on the subject, etc.